Brazilian multicenter study of association between polymorphisms in CRISPLD2 and JARID2 and non‐syndromic oral clefts. (21st June 2016) - Messetti, Ana Camila; Machado, Renato Assis; de Oliveira, Carine Ervolino; Martelli‐Júnior, Hercílio; de Almeida Reis, Silvia Regina; Moreira, Helenara Salvati Bertolossi; Persuhn, Darlene Camati; Wu, Tao; Coletta, Ricardo D.
Abstract : Background: Variants in the cysteine‐rich secretory protein LCCL domain containing 2 gene ( CRISPLD2 ) and in the jumonji, AT‐rich interaction domain 2 gene ( JARID2 ) were previously shown to influence non‐syndromic oral cleft susceptibility. Herein, we performed a case−control study to examine the potential association of single‐nucleotide polymorphisms (SNPs) in CRISPLD2 and JARID2 with non‐syndromic cleft lip and/or palate (NSCL/P) in the Brazilian population. Given the ethnicity‐dependent genetic predisposition to NSCL/P, we performed a structured analysis taking into account the genomic ancestry variation of each individual. Methods: Four SNPs in CRISPLD2 (rs1546124, rs8061351, rs2326398, and rs4783099) and four in JARID2 (rs915344, rs2299043, rs2237138, and rs2076056), that were previously reported to be associated with NSCL/P, were genotyped in 785 Brazilian patients with NSCL/P (549 with cleft lip with or without cleft palate‐NSCL ± P, and 236 with cleft palate only‐NSCPO) and 693 unaffected Brazilian controls. Genomic ancestry was assessed with a set of 40 biallelic short insertion/deletion variants previously validated as ancestry informative markers of the Brazilian population. Results: After adjustment of ancestry variations, allelic analysis revealed marginal associations between the CRISPLD2 rs4783099 T allele and increased risk for NSCPO (OR: 1.31, 95% CI: 1.05–1.62, P = 0.01) and between JARID2 rs2237138 and decreased NSCL ± P risk (OR: 0.80, 95% CI: 0.67–0.97, P = 0.02). Haplotype analysis indicated a lack of association between JARID2 haplotypes and non‐syndromic oral cleft risk. Conclusions: Our results suggest that CRISPLD2 rs4783099 may represent a risk factor for NSCPO while JARID2 rs2237138 shows a protective effect against NSCL ± P in the Brazilian population.